Nutraceutical and Cosmeceutical Products Containing Low Molecular Weight Peptides from Fermented Colostrum - Ionuț Moraru; Angela Moraru; Anca Oancea; Alexandra Gaspar-Pintiliescu; Viorica Coroiu; Laura Stefan; Andreea Iosăgeanu; Teodora Ciucan; Daniela Ilie; Cătălina Sanda; Ana-Maria Seciu-Grama (Proceedings, 2020)
Introduction: Nutraceuticals are food or parts of a food that provide medicinal or health benefits, including the prevention and treatment of disease. [...]